Adaptation Strategies of Smallholder Farmers to Climate Change and Variability: Evidence from Northern Ghana - M., John K.; ., Prince Maxwell Etwire; ., Yaw Osei-Owusu (Information Management and Business Review, 2013)
Farmers have been modifying their practices in order to deal with climate change and variability. Even though such practices have been documented in other parts of Africa, information on Ghana and particularly northern Ghana is scanty. This study examines the adaptation strategies of smallholder farmers to climate change and variability in northern Ghana. The paper is based on primary data collected through a household survey, community focus group discussions and key informant interviews in order to identify the adaptation responses of smallholder farmers in northern Ghana to climate change and variability. Several indigenous climate-related practices and technologies categorised into four strategies were identified. In addition, climate related technologies introduced by research, also categorised into four strategies, and were identified as being used by smallholder farmers in northern Ghana. The empirical results of the Friedman test indicates that timing of the onset of the rainy season which informed planting, and soil and plant health related strategies are the most important climate related strategies used by smallholder farmers in securing yield. The policy implication is that practical, timely and reliable information on the onset of the rainy season as well as region specific soil and plant health technologies should be generated and made available to smallholder farmers in northern Ghana to minimise the adverse impacts of climate change.